Nonlinear Heat Radiation Induces Thermal Rectifier in Asymmetric Holey Composites - Zhu, Weiwei; Wu, Gaomin; Chen, Hong; Ren, Jie (Frontiers in Energy Research, 2018)
Asymmetric design and nonlinearity are essential to give rise to thermal rectification. In addition to the linear Fourier’s law of thermal conduction, we introduce the nonlinear thermal radiation following Stefan–Boltzmann law to asymmetric holey composites to realize the thermal rectifier. The thermal rectification results from the competition between the linear thermal conduction and the nonlinear thermal radiation, which we explain as a thermal resistor network with the linear and nonlinear components connected in series-parallel. All the results are confirmed by an analytical model that is composed of one central nonlinear thermal radiation region sandwiched by two linear conduction regions with different conductances. We can get the optimal rectification effect around the room temperature when the temperature difference is fixed, which allows the application of the designed materials to energy-saving buildings.